1987
DOI: 10.1038/328616a0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 5 allele loss in human colorectal carcinomas

Abstract: That the sporadic and inherited forms of a particular cancer could both result from mutations in the same gene was first proposed by Knudson. He further proposed that these mutations act recessively at the cellular level, and that both copies of the gene must be lost for the cancer to develop. In sporadic cases both events occur somatically whereas in dominant familial cases susceptibility is inherited through a germline mutation and the cancer develops after a somatic change in the homologous allele. This mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
6

Year Published

1988
1988
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(142 citation statements)
references
References 0 publications
4
132
0
6
Order By: Relevance
“…It has been reported that the genes encoding two key enzymes in cholesterol synthesis are located in chromosome 5 (44,45), which has been shown to be the location of one of the genes involved in the adenoma-carcinoma sequence (46,47). It is possible that deletions in genes on chromosome 5 lead both to decreased cholesterol synthesis and to the progression of adenoma to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the genes encoding two key enzymes in cholesterol synthesis are located in chromosome 5 (44,45), which has been shown to be the location of one of the genes involved in the adenoma-carcinoma sequence (46,47). It is possible that deletions in genes on chromosome 5 lead both to decreased cholesterol synthesis and to the progression of adenoma to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…When tumours form while retaining the chromosome carrying the wild-type Apc allele, the expression of the Apc polypeptide is attenuated (¢gure 3). This loss of expression is not accompanied by any known mutation of the Apc gene: the wild-type DNA sequence at the Min site is retained, and no chain-terminating mutations of Apc are detected (A. R. Shoemaker, unpublished data scenario is currently mysterious, with several conceivable explanations: (i) the wild-type allele might be silenced by a stable epigenetic change, along lines initially suggested by Solomon, Bodmer and their colleagues (Solomon et al 1987); (ii) a speci¢c epigenetic mechanism, hypermethylation of the Apc promoter, might attenuate Apc expression (Hiltunen et al 1997); or (iii) a second locus that regulates the expression of Apc might be somatically mutated (Haber et al 1990). Consistent with this last possibility, the incidence of tumours retaining but not expressing an apparently normal Apc allele is increased by appropriately timed ENU treatment of AKRÁMin mice (A. R. Shoemaker, unpublished data).…”
Section: The Centrality Of the Apc Regulatormentioning
confidence: 91%
“…The presumption would then be that some fraction of non-hereditary colon cancers should show loss of heterozygosity for syntenic markers, the idea being that a somatic mutation had occurred at one copy of the gene, and a gross chromosomal event such as deletion, chromosomal loss or recombination had led to loss of the other normal copy. Solomon et al (1987) reported such loss at a frequency of 23%, or perhaps higher. Other investigators have since reported frequencies in the range of 19-36% (Law et al, 1988;Vogelstein et al, 1988 There is no information about the location of the nonpolyposis colon cancer, but one may begin by assuming that it is not on Sq.…”
Section: Wilms' Tumour and Rhabdomyosarcomamentioning
confidence: 96%